Food and urbanism : the convivial city and a sustainable future - Parham, Susan (Bloomsbury Academic, 2015)
"Cities are now home to over fifty per cent of the world's population, but the contribution of food to shaping cities is often overlooked. Food matters in designing and planning cities because how it is grown, transported, bought, cooked, eaten, cleaned up and disposed of has significant effects on creating a sustainable, resilient and convivial urban future. The book explores methods for extending the gastronomic possibilities of urban space - from the scale of the table to the metropolis. Using a wealth of examples from cities worldwide, the book explores how physical design and socio-spatial arrangements focused on food can help maintain socially rich, productive and sustainable urban space. Underpinning the book's analysis of food and cities is the view that decisions about a hyper-urban future should recognise the fundamental role of food. Food and Urbanism provides an original and new contribution to food scholarship; exploring some intriguing research questions about the ways that food, urbanism and sustainable conviviality interconnect"--